Modern nematode-resistant varieties of potatoes in the conditions of the North - T. E. Zhigadlo (Овощи России, 2023)
Golden potato nematole (Globodera rostochiensis Woll.) is a phytoparasite, a microscopic worm that causes potato globoderosis. As a result, the yield is sharply reduced, small tubers are formed, and then the complete death of plants. The damage caused by the golden potato nematode manifests itself when the soil is infected with larvae in the amount of 1 thousand pieces or more in 100 cm3. The decrease in yield in areas of severe infection can reach from 70 to 90%. Early potato varieties are most affected. The best way to protect potato varieties from globoderosis is to use in the production of varieties resistant to golden potato nematode. The aim of the research was to study nematode-resistant potato varieties in the Murmansk region.Methods. In 2016-2020, 49 potato varieties resistant to globoderosis were studied on the experimental field of the Polar Experimental Station of VIR according to the main biological and economically valuable characteristics. The size of the plot was 0,05 ha, the area of plant nutrition was 70x30 cm. Planting of varieties was carried out in early June. The samples were planted in the field in a row of 10 plants of each variety. Every 10 samples, the Khibinskiy ranniy variety was located. All accounts are performed according to the VIR methodology.Results. Phenological observations have shown varieties with short periods of passage of phenological phases: Diamond, Grand, Pershatsvet, Khibinskiy ranniy, Roeslau. Berry formation was of the Labadia variety. The yield on the 60th day from planting was 531.7-741.7 g / bush (the maximum yield of the Madeleine variety). On the 90th day from planting, the yield of the varieties was in the range of 747,5-1153,0 g/bush (the maximum for the Eurasia variety). Starch content varied from 8,3% (Arrow grade) up to 20,4% (Albatros). According to disease resistance, the varieties Grand, Gusar, Eurasia, Harmony, Colorit, Rasinka, Albatros, Angela, Courage are distinguished. Conclusion. Samples of the world potato collection have been studied; sources of valuable traits that can be used in breeding work to create new varieties suitable for cultivation in the Far North have been identified.